Characteristics, Structure, and Effects of an On-Line Tool for Improvement in Adolescents’ Competency for Interaction With Alcohol: The e-ALADOTM Utility - de la Fuente, Jesús; Cubero, Inmaculada; Peralta, Francisco Javier; Sánchez, Mari Carmen; Salmerón, Jose Luis; Fadda, Salvatore (Frontiers in Psychology, 2019)
This research report aims to present the characteristics, structure and effects of a psychoeducational technological innovation (called the e-ALADO Program) for the prevention of alcohol intake in adolescents. Based on the Competency model for interaction with alcohol, this program consists of a total of 24 lessons that promote conceptual, procedural and attitudinal learning, in ICT format (www.alado.es). The hypothesis of this validation study established that adolescents treated with the program would improve their levels of competence and their interaction behavior with alcohol, depending of their personal level of self-regulation. A total of 148 adolescents from 12 to 16 years of age from three Spanish educational centers with different sociocultural contexts participated. A quasi-experimental methodology with repeated measures and use of inferential analysis was used (ANOVAs and MANOVAs). The results show a main principal effect of the Treatment variable, of the Self-Regulation Level variable, and an interaction effect of Treatment x Self-regulation in the the conceptual and attitudinal subcompetence for interaction with alcohol. The results are discussed in the face of new technological developments that allow the evaluation and intervention in the prevention of alcohol intake with adolescents. An important implication of this work is related to the importance of self-regulation as a psychological variable. Also, the suitability of psychoeducational interventions with new technological formats in the prevention of adolescents' alcohol intake as entrepreneurial activity.